Estudio de prefactibilidad para la instalación de una empresa comercializadora de productos personalizados a través de una plataforma móvil - Fidel Ponce, Diego Ricardo (2020)
This research work develops a pre-feasibility study of a company that sells personalized products through a mobile platform. This consists of nine chapters, in this executive summary the different points developed will be explained. The work is carried out following the problem of a constantly expanding technological market and seeks to demonstrate the economic, commercial, technical and financial viability for the implementation of a service dedicated to the sale of personalized products. The market study determined that the specific demand of the project is equivalent to 14,352 units sold in the first year and 28,769 units in the last year. The districts of La Molina and Santiago de Surco are evaluated as location alternatives for commercial offices. Based on the factors of proximity, cost and competition, the location selected was the office itself in the district of La Molina. Likewise, the relationship with the size of the market, resources, technology, investment and the breakeven point is developed, which turned out to be 17,650 cups and 9,669 poles per year. It was determined that the human resources necessary to provide the service are a general manager, a designer, a customer service coordinator, an office manager and a reception manager. With reference to the financial economic analysis, an investment of 121,059 soles was estimated, financing 80% at a rate of 20% at 5 years with constant installments, the economic NPV was 92,453 soles and the IRR of 44.7% calculated at 5 years and With a COK of 30.14%, the Financial NPV was 107,538 soles, also at 5 years and the IRR of 87.76% Finally, the following indicators were obtained for the social evaluation: an aggregate value of 131,750 soles, the capital product ratio is 1.08 soles, the capital intensity is 0.91 and the capital density is equal to S / 26,902.